Experimental investigation on a base isolation system incorporating steel-Teflon sliders and pressurized fluid viscous spring dampers. - Sorace, Stefano
An experimental investigation on a base isolation system incorporating stainless steel-Teflon bearings as sliders, and pressurized fluid viscous spring dampers, is presented in this paper. In the system examined, dampers are connected to the base floor of an isolated building to provide the desired passive control of response in the superstructure, as well as to guarantee that it re-centres completely after the termination of a seismic action. Two types of experiments were conducted : sinusoidal and random cyclic tests and a pseudodynamic test in 'substructured' configuration. The cyclic tests were aimed at characterizing what follows : the hysteretic and strain rate dependent response of the considered highly non-linear spring dampers; the normal pressure and strain rate dependent frictional behavior of steel Teflon bearings, manufactured in compliance with the latest standards for this class of sliders; and the combined response of their assembly. The pseudodynamic test simulated the installation of the protection system at the base of 2:3 scale three storey steel frame structure, already tested in unprotected conditions by an earlier experimental campaign. Among other findings, the results of the performed tests, as well as of relevant mechanical interpretation and numerical simulation analyses, confirmed the linear additive combination of the dissipative actions of spring dampers and sliders in this mixed installation, and the high protective performance of the considered base isolation/supplemental damping system in a realistic earthquake simulation.
Keywords: Seismic protection; Base isolation; Supplemental damping; Sliding bearings; Fluid viscous devices; Cyclic tests; Pseudodynamic tests; Substructuring